ANALISIS PORTOFOLIO SAHAM OPTIMAL DENGAN METODE MARKOWITZ DAN MODEL INDEKS TUNGGAL PADA SAHAM PERBANKAN BURSA EFEK INDONESIA - Muhammad Farhan Mingka; Riri Syafitri Lubis (LPPM Universitas Bina Bangsa, 2023)
A portfolio is a combination of assets with a desired rate of return as well as risks that can be minimized by spreading risks across different assets. The LQ45 index contains 45 companies whose shares have a market capitalization and a high level of liquidity. The population used in this study is 7 banking stocks that are on the LQ45 index. This study aims to develop an optimal portfolio using the Markowitz Method and the Single Index Model, then compare the results of the two. The combination of stocks produced using the Markowitz method consists of 2 BMRI and BBNI stocks with a portfolio return rate of 0.0247 and a risk of 0.0033. While the combination of stocks produced using the Single Index Model consists of 5 stocks, namely BMRI, BRIS, BBRI, BBNI, and BBCA stocks with a portfolio return rate of 0.019 and a portfolio risk of 0.0018. So a good model to use is the Single Index Model because the risk is smaller than using the Markowitz method